Comparing effects of Nordic hamstring exercise in combination with electrical stimulation and in combination with the FIFA 11+ program on footballers with strained hamstring muscles - Kaewsri, Amornrat; Boonyarom, Onuma; Srisupornkornkool, Kanokwan (Chulalongkorn Medical Journal, 2021)
Background: Football is a popular sport with many subjects. Hamstring muscle strain injury is one of the most common injuries. This type of injury occurs at a high rate and has a high re-injury rate, which results in a loss of training and competition time. However, an efficient prevention and rehabilitation program could help to reduce the impact of injuries on football athletes. Objectives: This study aimed to investigate and compare the effects of Nordic hamstring exercise in combination with electrical stimulation and in combination with the Federation International de Football Association 11+ program on football athletes with hamstring muscle strain. Methods: Sixteen footballers from Kasetsart University’s Kamphaengsaen campus, aged 18 - 25 years old (mean age = 19.9 1.5 years old), participated in the study. Through random sampling, the subjects were assigned to a group involving Nordic hamstring exercise combined with either electrical stimulation or FIFA 11+. Results: The results showed that, after 6 weeks of training, both groups showed improvements in the strength of strained hamstring muscles (Nordic hamstring exercise with electrical stimulation was 9.8 2.4 kg before training and 17.7 2.0 kg on week 6; Nordic hamstring exercise with FIFA 11+ was 9.8 2.8 kg before training and 15.8 2.3 kg on week 6), but there was no significant difference between the 2 groups. Conclusion: This study concluded that the training program used for either group could increase the strength of strained hamstring muscles.